1838 Ark Rev. Stat. 733-34 - (:unkn) unknown (My University, 1837)
§ 23: Prohibited possession of offensive or defensive weapon without written permission of his master. Violators shall have the weapon seized and whipped not exceeding thirty stripes.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES